Haploinsufficiency of the Parkinson’s disease gene synaptojanin1 is associated with abnormal responses to psychomotor stimulants and mesolimbic dopamine signaling - Mejaes, Jennifer I.; Saenz, Jacqueline; O’Brien, Chris; Pizzano, Carina M.; Pan, Ping-Yue; Barker, David J. (Frontiers in Behavioral Neuroscience, 2024)
The synaptojanin-1 (SYNJ1) gene is known to be important for dopamine-related disorders.Recent evidence has demonstrated that Synj1 deficient mice (Synj1 +/-) have impairments in dopaminergic synaptic vesicular recycling. However, less is known about how Synj1 deficits affect the mesolimbic system, reward processing, and motivated behavior. To examine the role of the Synj1 gene in motivated behavior, we subjected male and female Synj1 +/-and Synj1 +/+ mice to a battery of behavioral tests evaluating hedonic responses, effortful responding, and responses to psychomotor stimulants. We observed that Synj1 +/-mice exhibit few differences in reward processing and motivated behavior, with normal hedonic responses and motivated responding for sucrose. However, male but not female Synj1 +/-demonstrated an attenuated conditioned place preference for cocaine that could not be attributed to deficits in spatial memory. To further understand the dopamine signaling underlying the attenuated response to cocaine in these mutant mice, we recorded nucleus accumbens dopamine in response to cocaine and observed that Synj1 +/-male and female mice took longer to reach peak dopamine release following experimenter-administered cocaine. However, female mice also showed slower decay in accumbens dopamine that appear to be linked to differences in cocaine-induced DAT responses. These findings demonstrate that SYNJ1 deficiencies result in abnormal mesolimbic DA signaling which has not previously been demonstrated. Our work also highlights the need to develop targeted therapeutics capable of restoring deficits in DAT function, which may be effective for reversing the pathologies associated with Synj1 mutations.